Electrochemical Study of Interaction between Imidazole-Based-Ionic-Liquid and Light Petroleum in Oil/Water Emulsion - Villalobos Neri, E.E.; Páramo García, U.; Mayen Mondragon, R.; Gallardo Rivas, N.V. (2021)
In the present work, the binding capacity of a 1-methyl-3-hexylimidazolium p-toluenesulfonate ionic liquid to Aragon light oil within a 70/30 oil/water emulsion was studied by cyclic voltammetry. The imidazole-based ionic liquid was synthesized by anion interchange reaction. Its chemical structure was confirmed by Fourier-Transform Infrared Spectroscopy and Nuclear Magnetic Resonance. Its Critical Micelle Concentration (CMC) in water was determined by Conductimetry, Ultraviolet-Visible Spectroscopy and Cyclic Voltammetry. The ionic-liquid-to-oil binding-constant and binding-free-energy were determined from the dependence of the voltammogram anodic-peak-current with the ionic liquid concentration in the emulsion. The diffusion coefficient of the free and bound forms of the oil within the emulsion were determined from the Randles-Sevcik equation. The measurements led to a CMC value of approximately 152 mg/L and a binding constant of 0.98x104 M-1, corresponding to a binding free energy of -22.78 KJ/mol. The negative value of the latter confirmed the ionic liquid spontaneously binds to the oil phase. The oil-droplets diffusion coefficient showed a 2.5-fold increase (up to 4.631x10-7 cm2/s) due to incorporation of the ionic liquid molecules. The information gathered can be helpful to design more efficient remediation processes of oil-contaminated water, as well as to improve the design of ionic liquid molecules, and to study their interaction with different oil components.